Reading narratives whose protagonists experience emotions: fMRI evidence of down-regulation of thalamic regions associated with anxiety disorder. (May 2022) - Toazza, Rudineia; Buchweitz, Augusto; Franco, Alexandre Rosa; Esper, Nathalia Bianchini; Salum, Giovanni Abrahão; DeSousa, Diogo; Dalle Molle, Roberta; Rodrigues, Danitsa Marcos; Reis, Roberta Sena; Mucellini Lovato, Amanda Brondani; Flores, Suzielle Menezes; Pérez, Juliano Adams; et al.
Abstract: Introduction: The goal of the present study was to investigate the association of anxiety disorder and brain activation while reading stories whose outcomes show protagonists experiencing emotions. Methods: We carried out an fMRI study of 28 adolescents and young adults (14–22 years; 14 Anxiety Disorder Participants and 14 Controls) who read short narratives with angry, happy, sad, or neutral. outcomes We used mixed analyses of variance to test the effects of Group (anxiety/comparison), Emotion (angry/happy/sad, neutral) and Group by Emotion interaction. Results: A significant Group by Emotion interaction was identified in a thalamic-region cluster of brain activation. Participants with anxiety disorders showed significantly less thalamic activation relative to controls. The interaction was identified by contrasting emotional vs. neutral passages. There was also a main effect of emotional passages versus neutral passages in a network of anterior and posterior areas of the brain, which included mid and superior temporal, left inferior frontal, left inferior parietal and dorsomedial prefrontal areas, some of which are among brain regions identified in studies of understanding the mind of a protagonist. Finally, we did not find a main effect of Group. The results suggest that anxiety in adolescents and young adults is associated with modulating activation of thalamic regions when processing emotions of fictional characters. The thalamic cluster identified in the present study corroborates previous studies that have addressed brain activation associated with anxiety. Highlights: Anxiety disorders associated with down-regulation of activation in a thalamic cluster. Narratives with emotional content elicited more activation of language and social cognition related areas of the brain. More activation was shown for reading of the critical sentence (overt description of emotions) of the passage.